2010
DOI: 10.1177/1066480710364479
|View full text |Cite
|
Sign up to set email alerts
|

Using Bowen Theory to Examine Progress in Couple Therapy

Abstract: The purpose of this investigation was to test whether differentiation of self in couple members affected the trajectories of marital satisfaction, marital commitment, and individual well-being across the early sessions of therapy while taking into account the level of distress the couple was experiencing. The sample consisted of 127 couples seeking services at an on-campus couple and family therapy clinic. A latent growth curve modeling approach was used for data analysis. Even though differentiation of self o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…Relatedly, I‐positioning may allow individuals in committed relationships to be more supportive of their partner's independence and separate leisure time, which may have residual effects on the quality of shared leisure time as a couple. Supporting our findings, Bartle‐Haring and Lal () found I‐positioning to be significantly associated with relationship satisfaction through partner effects in heterosexual relationships; husbands' level of I‐positioning was associated with lower stress in wives. Our findings further support the significance of I‐positioning in intimate relationships by demonstrating that I‐positioning works through leisure satisfaction to positively affect dyadic adjustment.…”
Section: Discussionsupporting
confidence: 87%
“…Relatedly, I‐positioning may allow individuals in committed relationships to be more supportive of their partner's independence and separate leisure time, which may have residual effects on the quality of shared leisure time as a couple. Supporting our findings, Bartle‐Haring and Lal () found I‐positioning to be significantly associated with relationship satisfaction through partner effects in heterosexual relationships; husbands' level of I‐positioning was associated with lower stress in wives. Our findings further support the significance of I‐positioning in intimate relationships by demonstrating that I‐positioning works through leisure satisfaction to positively affect dyadic adjustment.…”
Section: Discussionsupporting
confidence: 87%
“…In a series of studies negative links were found between differentiation of self and various anxieties, such as, trait anxiety [8], separation anxiety [5,6,12], social anxiety [7], psychiatric symptoms, depression symptoms [3,14,15] physiological symptoms [10,16], stress [17], and over involved counter-transference behaviors [18]. In addition, positive associations were found between differentiation of self and psychological adaptation, the ability to solve social problems [19], mental wellbeing and psychological health [3,14,20], marital satisfaction [4], and life satisfaction [21,22].…”
Section: Differentiation Of Self and Satisfaction With Lifementioning
confidence: 99%
“…Inventory-Revised We assessed levels of differentiation of self using the DSI-R [8], translated into Hebrew [4,17] and to Arabic for the purpose of the present study, using Brislin's backtranslation method for cultural research [42]. First, a neutral mother-tongue quality Arabic-English speaker translated it from English to Arabic.…”
Section: The Differentiation Of Selfmentioning
confidence: 99%
“…Previous studies have shown health status (Toviessi, 2003), coping (Toviessi, 2003), and relationship satisfaction (Bartle-Haring & Lal, 2010; Durtschi, 2007) to be related to differentiation; however, in those studies, each of these are with general samples. The main purpose of this article is to use differentiation as a framework to study maternal well-being, as it relates to relationship satisfaction for new mothers: to further understanding of first-time mothers’ differentiation, perceived health during pregnancy and family coping, as it relates to relationship satisfaction during the postpartum period.…”
mentioning
confidence: 96%